COMPREHENSION DES TEXTES FRANÇAIS CHEZ LES ELEVES DE DEUXIEME ANNEE DES HUMANITES PEDAGOGIQUES DE QUELQUES ECOLES DE LA COMMUNE KASUKU, VILLE DE KINDU. - Alphonse, Okamba Mundala (IJRDO- Journal of Educational Research, 2022)
The main objective of this research is to evaluate the level of performance of syntactic and morphological entries of words in a text in second year students of pedagogical humanities. The analysis of the data was carried out by calculating the arithmetic mean, standard deviation, median, coefficient of variation, yield, analysis of variance. In a global way, the comprehension of the syntactic and morphological entries for the seen text is sufficient, the output is higher than 50%. For the unseen text, the comprehension of the syntactic and morphological entries is insufficient, the output is lower than 50%. The variable institution of attendance had no effect on performance. To improve the learning of reading instruction, teachers can frequently use the direct method combined with the audio-oral and audio-visual method, the global method. Emphasize comprehension by subjecting learners to the cloze exercise.